Nonconformism, Social Identity, and Self-efficacy of Women Leaders of Thematic Villages - Bernacka, Ryszarda Ewa; Mazurek-Kusiak, Anna; Korcz, Natalia; Kobyłka, Agata (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
The specific aim of this study was to explore whether traits typified as particularly expected in the management of thematic villages: nonconformism, social identity, and self-efficacy are present in their 57 female leaders. The following questionnaires were applied: Creative Behavior Questionnaire (CBQIII); J.E. Cameron's Social Identity Scale (STS) and Generalized Self-Efficacy Scale (GSES). The analysis revealed significant relationships between nonconformism and self-efficacy. Nonconformism was negatively associated with the social identity of leaders of thematic villages. Social identity was negatively connected to self-efficacy, especially with its component centrality.